Jordanian Case Law on Recognition and Enforcement of Foreign Judgments and Foreign Arbitral Awards - Aldmour, Abdullah (Dirasat: Shari'a and Law Sciences, 2021)
In international litigation or arbitration, judgments or awards can often be enforced in a jurisdiction other than the one where they were made. Foreign judgments and foreign awards will have to be recognized and enforced by the competent Jordanian jurisdiction through an exequatur. This article provides a comprehensive overview of the existing legislative framework pertaining to recognition and enforcement of foreign judgments, including foreign court orders and international arbitral awards, in Jordan. By reference to Jordanian case law, the article highlights the legal practice in Jordan and the approach of the Jordanian Court of Cassation. A systematic analysis of the Jordanian case law relating to enforcing foreign judgments over the past years shows that the Court of cassation has consistently shown a positive trend towards enforcing foreign judgments and arbitral awards. Nonetheless, the enforcement process is lengthy, with the judgment creditor having recourse to multiple levels of appeal and possibly facing some procedural and substantive concerns.